2022
DOI: 10.3390/ani12020170
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Feeding Behaviors Collected from an Automated Milk Feeder and Neonatal Calf Diarrhea in Group Housed Dairy Calves: A Case-Control Study

Abstract: The objective of this case-control study was to determine if feeding behavior data collected from an automated milk feeder (AMF) could be used to predict neonatal calf diarrhea (NCD) in the days surrounding diagnosis in pre-weaned group housed dairy calves. Data were collected from two research farms in Ontario between 2017 and 2020 where calves fed using an AMF were health scored daily and feeding behavior data (milk intake (mL/d), drinking speed (mL/min), number of rewarded or unrewarded visits) was collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…The spectrum of pathogenic microflora in different dairy farms is different, and therefore there is a problem of prevention and treatment of diarrhoea in calves (Conboy et al, 2022). Antibiotics and sulphonamides are usually used for this purpose, which are included by the World Health Organisation in the list of "highest priority" agents due to their danger to animal and human health.…”
Section: Introductionmentioning
confidence: 99%
“…The spectrum of pathogenic microflora in different dairy farms is different, and therefore there is a problem of prevention and treatment of diarrhoea in calves (Conboy et al, 2022). Antibiotics and sulphonamides are usually used for this purpose, which are included by the World Health Organisation in the list of "highest priority" agents due to their danger to animal and human health.…”
Section: Introductionmentioning
confidence: 99%
“…Early detection of sick calves kept in large groups may be difficult, so frequent and routine monitoring of calves is highly recommended (Van Metre et al., 2008 ). Strategies to detect these animals should include indicators collected by automated milk feeders (Borderas et al., 2009 ; Morrison et al., 2021 ; Conboy et al., 2022 ).…”
Section: Assessmentmentioning
confidence: 99%
“…Conboy et al [ 39 ], in a cross-sectional study involving 523 observations, reported a 63% reduction in daily milk intake of calves with bovine respiratory disease (BRD) and 57% in calves with neonatal calf diarrhoea (NCD). In another study, calves with NCD had a significative decrease in milk intake on the day of diagnosis, 5 days after (observed daily by faecal consistency), and a tendency for −1 d ( p = 0.09); as for rewarded visits, diarrheic calves presented fewer visits at −1 d and 0 d than healthy calves, but more visits at 3 d and a tendency at 4 d [ 40 ]. Moreover, the parallel sensitivity and specificity on the day of diagnosis using milk intake and rewarded visits were not satisfactory (Se of 69% and Sp of 22%).…”
Section: Technological Applications To Monitor Calves’ Health and Wel...mentioning
confidence: 99%